A Matter of Framing: Explaining the Failure of Post‐Islamist Social Movements in the Arab Spring. (1st August 2016) - Hoyle, Justin A.
Abstract: Shortly after the Arab Spring began in 2010, multiple scholars noted that the dominant discursive trend present within these protests was that of post‐Islamism. Post‐Islamism is broadly defined as an ideology seeking to establish a democratic state within a distinctly Islamic society. Despite the presence of post‐Islamist opportunity structures, social movements embodying post‐Islamist principles have had little success consolidating power. The theoretical argument presented here is that the failure of these movements is the result of inherent flaws within post‐Islamist frames. Specifically, this study posits that unlike traditional Islamist frames (i.e., frames emphasizing the creation of a state governed by Shari'a) post‐Islamist frames limit the ability of movements' to monopolize religion as a cultural asset. As such, when post‐Islamist movements face political challenges during contentious periods they cannot rely on nontemporal legitimacy to retain power. Additionally, the challenging task of integrating Islamic and democratic frames in contentious moments renders post‐Islamist movements susceptible to counterframing. The preceding claims will be tested through a comparative analysis of the Iranian Hierocracy (1977–1979), and the Egyptian Muslim Brotherhood (2011–2014). Comparing the experiences of a post‐Islamist movement (Brotherhood) with that of an Islamist movement (Hierocracy) will explicate the flaws within post‐Islamist frames.